Politik der ,Glückskulturen' NS-Deutschland und die Schweiz, 1933-1945 - Haffter, Isabelle (De Gruyter, 2021)
Knowledge about "happiness" means power. For the self-portrayal of a nation and its moral system, knowledge about happiness can be used and reinterpreted as an emotional-political instrument of power. Isabelle Haffter demonstrates the constructedness of happiness knowledge by examining examples from politics, science and the performing arts as part of a transnational history of knowledge and emotions about cultural nationalisms.